A review of analytical and semi-empirical approaches for analysis of flutter aerodynamic instability (Far Eastern Federal University: School of Engineering Bulletin, 2023)
Estimation of the possibility of aerodynamic instability plays one of the important roles in the design of various structures. Current paper presents an overview of existing analytical (including semi-analytical and semi-empirical) flutter models and methods for flutter limit (flutter critical velocity) estimation, which formed the basis for engineering analysis of flutter instability of structures. Analytical models of flutter are used as a part of the flutter analysis performed experimentally and/or by using numerical methods. In addition to the review of analytical and semi-empirical methods for assessing flutter instability, a brief analysis of regulatory documents (both domestic and foreign design codes) is presented. This review showed that in all the design codes considered, flutter is recognized as a dangerous and unacceptable aeroelastic phenomenon, however, no method for analyzing of this phenomenon is proposed, and only recommendations are given for assessing the possibility of flutter occurrence based on the characteristics of structures. For structures subject to flutter, a recommendation is made for additional studies of this phenomenon based on wind tunnel tests or with the help of a specialist. The review of existing analytical and semi-empirical flutter models and methods for estimating the flutter limit presented in the paper indicates the possibility and necessity of updating domestic design codes and standards in terms of flutter analysis.